Barriers to care in episodic and chronic migraine: Results from the Chronic Migraine Epidemiology and Outcomes Study. Issue 4 (1st April 2021) - Buse, Dawn C.; Armand, Cynthia E.; Charleston, Larry; Reed, Michael L.; Fanning, Kristina M.; Adams, Aubrey Manack; Lipton, Richard B.
Abstract: Objective: To assess rates of and factors associated with traversing fundamental barriers to good medical outcomes and pharmacologic care in individuals with episodic migraine (EM) and chronic migraine (CM), including socioeconomic status and race. Background: Barriers to good outcomes in migraine include the lack of appropriate medical consultation, failure to receive an accurate diagnosis, not being offered a regimen with acute and preventive pharmacologic treatments (if indicated), and not avoiding medication overuse. Methods: The Chronic Migraine Epidemiology and Outcomes (CaMEO) Study was a longitudinal Internet‐based survey. Respondents who met criteria for migraine consistent with the International Classification of Headache Disorders, 3rd edition, had a Migraine Disability Assessment score ≥ 6, and provided health insurance coverage status were included in this analysis. Successfully traversing each barrier to care and the effects of sociodemographic characteristics were examined. Results: Among 16, 789 respondents with migraine, 9184 (54.7%; EM: 7930; CM: 1254) were eligible. Current headache consultation was reported by 27.6% (2187/7930) of EM and 40.8% (512/1254) of CM respondents. Among consulters, 75.7% (1655/2187) with EM and 32.8% (168/512) with CM were accurately diagnosed. Among diagnosed consulters, 59.9% (992/1655) with EM and 54.2% (91/168) with CM reported minimally appropriate acute and preventive pharmacologic treatment. Among diagnosed and treated consulters, in the EM group 31.8% (315/992) and in the CM group 74.7% (68/91) met medication overuse criteria. Only 8.5% (677/7930) of EM and 1.8% (23/1254) of CM respondents traversed all four barriers. Higher income was positively associated with likelihood of traversing each barrier. Blacks and/or African Americans had higher rates of consultation than other racial groups. Blacks and/or African Americans and multiracial people had higher rates of acute medication overuse. Conclusions: Efforts to improve care should focus on increasing consultation and diagnosis rates, improving the delivery of all appropriate guideline‐based treatment, and avoidance of medication overuse.